The relationship between Information Technology (IT) resources and employee’s perfomance at Rintiz Group Berhad Ayer Keroh Melaka / Nur Liana Kamarudin - Kamarudin, Nur Liana (Faculty of Business and Management, 2014)
The study is to investigate the relationship between information technology (IT) resources and Employees' Performance in Rintiz Group Berhad Ayer Keroh Melaka. This research were conducted based on three independent variables which are IT infrastructure, IT Application and IT Knowledge. This paper examine bow these resources affect the employees' performance. This study is use stratified sampling technique to collect data. The finding shows the relationship between IT resources and employees' performance.